Trust or Property Rights? Can Trusted Relationships Substitute for Costly Land Registration in West African Cities? - Letrouit, Lucie; Selod, Harris (World Bank, Washington, DC, 2020)
The paper studies the market failures associated with land tenure insecurity and information asymmetry in an urban land use model, and analyzes households' responses to mitigate tenure insecurity. When buyers and sellers of land plots can pair along trusted kinship lines whereby deception (the non-disclosure of competing claims on a land plot to a buyer) is socially penalized, information asymmetry is attenuated, but overall participation in the land market is reduced. Alternatively, when owners can make land plots secure by paying to register them in a cadaster, both information asymmetry and tenure insecurity are reduced, but the registration cost limits land market participation at the periphery of the city. The paper then compares the overall surpluses under these trust and registration models and under a hybrid version of the model that reflects the context of today's West African cities where both registration and trusted relationships are simultaneously available to residents. The analysis highlights the substitutability of trusted relationships to costly registration and predicts the gradual evolution of economies towards the socially preferable registration system if registration costs can be sufficiently reduced.